The Social Construction of Dogs and Its Implications for Rabies Prevention Strategies (Journal of Social And Education Research, 2023)
Rabies remains a significant public health concern, particularly in regions with high dog populations. This study examines how social constructions of dogs influence rabies prevention strategies, focusing on community perceptions, cultural norms, and human–dog interactions. A systematic review of 15 studies published between 2010 and 2023 was conducted to identify factors affecting responsible dog ownership, vaccination uptake, and public engagement in rabies control. The findings indicate that social and cultural beliefs significantly shape behaviors related to dog management, including vaccination compliance and post-exposure practices. Effective rabies prevention requires integrating biomedical interventions with culturally sensitive approaches, community participation, and education programs that address local perceptions of dogs. Policies that respect community norms while promoting responsible ownership and vaccination are crucial for sustainable rabies control. The study highlights that understanding the social construction of dogs provides a comprehensive framework for designing inclusive, context-specific, and effective rabies prevention strategies.